Falling in (to) Color: Chromophilia and Tom Ford's A Single Man (2009) (The moving image, 2015)
Tom Ford's A Single Man (2009) suggests that falling in (to) color is a falling into embodiment, sensuality, and the pain of a lover's loss. The film shows the last twenty-four hours of a character's life as a gradual reawakening or attunement to the surfaces of the world. The film's fetishistic attention to texture, detail, and color suggests that cinema's capacity to isolate, focalize, and reframe enables a phenomenal openness to the world that is not unlike the experience of falling in love, while its celebration of color aesthetics-its chromophilia-stages three different modalities in the history of color. First, its production design, technological capacities, and selective color saturation and desaturation exemplify the contemporary era's digital capacity to manipulate color, while simultaneously signaling a reflexive anxiety about the problem of color stability for analog film, with implications for the digital era. Second, the intermedial color design of the film's period setting in the early 1960s nostalgically mourns the passing of an earlier technological regime in which Technicolor was marked as fantastic, at the very historical moment when cinema and television shifted from black and white to Eastman Color as normative register. Third, in its pop art-inflected attention to chromatic surface and its textual allusions to Aldous Huxley's novels and to psychedelic vision, it explores new cultural concerns with perception and the expansion of consciousness. A Single Man aestheticizes a contemporary shift in the moving image from actuality to potentiality as one in which color acts as a signifier of appearance and disappearance, reflexively foregrounding the materiality of surface. By extension, through its progressive saturation and desaturation (or color "blooming"), it draws attention to the fragile and fugitive nature of analog color processes, yet also promises through its digital capacities that all might be retroactively restored.
https://katalog.adlr.link/Record/ai-68-OLC196124862X